Transpiration in Quercus suber trees under shallow water table conditions: the role of soil and groundwater - Pinto, Clara A.; Nadezhdina, Nadezhda; David, Jorge S; Kurz-Besson, Cathy; Caldeira, Maria C; Henriques, Manuel O; Monteiro, Fernando G; Pereira, João S; David, Teresa S (Hydrological Processes, 2013)
Water is one of the major environmental factors limiting plant growth and survival in the Mediterranean region. Quercus suber L. woodlands occupy vast areas in the Iberian Peninsula, frequently under shallow water table conditions. The relative magnitude of soil and groundwater uptake to supply transpiration is not easy to evaluate under these circumstances. We recently developed a conceptual framework for the functioning of the root system in Q. suber that simulates well tree transpiration, based on two types of root behaviour: shallow connected and deep connected. Although this significantly improved knowledge on the functional traits of Mediterranean Q. suber, the approach has the limitation of requiring root sap flow data, which are seldom available. In this work, we present alternative methodologies to assess if trees are connected to groundwater and to estimate the soil and groundwater contributions to tree transpiration. We provide evidence on the tree unrestricted access to groundwater solely based on meteorological, stem sap flow and leaf water potential data. Using a soil mass balance approach, we estimated the yearly soil and groundwater contributions to tree transpiration: 69.7% and 30.3%, respectively. Groundwater uptake became dominant in the dry summer: 73.2% of tree transpiration. Results reproduce extremely well those derived from root modelling. Because of its simplicity both in formulation and data requirements, our approach is potentially liable to be adapted to other groundwater- dependent Mediterranean oak sites, where interactions between land use and water resources may be relevant.
Keywords: Cork oak; ecohydrology; sap flow radial profile; tree water sources; tree water use; water balance

Establishing grazing and grazing-excluded patches increases plant and invertebrate diversity in a Mediterranean oak woodland - Bugalho, Miguel N; Lecomte, Xavier; Gonçalves, Merícia; Caldeira, Maria C; Branco, Manuela (Forest Ecology and Management, 2011)
Grazing is a global, dominant land use affecting biodiversity and ecosystem processes. In Mediterranean ecosystems grazing is a major ecological and evolutionary driver but, surprisingly, there is little information on the use of grazing as a tool to manage biodiversity in these ecosystems. We conducted an experiment to assess if establishing grazing and small scale grazing-excluded areas would increase plant and invertebrate diversity in a Mediterranean evergreen oak woodland. Plant community traits were different between treatments. Biomass of herbs (176.7±18.3 gm−2 vs 100.4±10.6 gm−2) and litter (291.0±38.3 gm−2 vs 186.8±26.4 gm−2), as well as the total cover of legumes (0.83±0.05 vs 0.91±0.03) were higher, and the proportion of bare ground (0.83±0.05 vs 0.91±0.03) was lower, in ungrazed plots. There were no differences in the number of plant species between treatments. Some plant species and invertebrate taxa were recorded exclusively in grazed or ungrazed plots. Invertebrate detritivores and sap sucking insects were more abundant in ungrazed plots. Ant assemblages were functionally different between treatments: Honeydew-gatherer ants were associated with ungrazed and higher plant biomass plots, and seed-eaters as well as aggressive predator ant species were associated with grazed, open habitat, plots. Management practices that maintain grazing and small scale grazing-excluded areas can increase habitat heterogeneity and promote herbaceous plant and invertebrate diversity at the local level.
Keywords: Cork oak; Deer; Grazing management; Holm oak; Land-use; montados